2005
DOI: 10.1177/0363546504270567
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Short Form-36 and Disability Status with Outcomes of Arthroscopic Acetabular Labral Debridement

Abstract: The Short Form-36 demonstrated good correlation with the modified Harris hip score for measuring outcomes after arthroscopic partial limbectomy. Arthroscopic debridement yielded a high percentage of good results when patients undergoing disability evaluations were excluded. Disability status may be a negative predictor of success after hip arthroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 29 publications
(52 reference statements)
2
92
1
Order By: Relevance
“…Meftah et al [18] and Farjo et al [6] found radiographic OA and arthroscopically determined femoral and acetabular cartilage degeneration correlated with postoperative self-reported symptoms and function among patients who underwent labral débride-ment (R 2 = 0.31) or repair of tears, respectively. Studies on outcomes after arthroscopic correction of FAI have found negative influences of OA on postoperative outcomes [14,20,21]. Preoperative radiographic joint space narrowing, together with preoperative MHHS score, and labral débridement or repair, predicted 35% of postoperative MHHS [20], and generalized severe cartilage lesions intraoperatively led to high rates of arthroplasty within 3 years of arthroscopy [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meftah et al [18] and Farjo et al [6] found radiographic OA and arthroscopically determined femoral and acetabular cartilage degeneration correlated with postoperative self-reported symptoms and function among patients who underwent labral débride-ment (R 2 = 0.31) or repair of tears, respectively. Studies on outcomes after arthroscopic correction of FAI have found negative influences of OA on postoperative outcomes [14,20,21]. Preoperative radiographic joint space narrowing, together with preoperative MHHS score, and labral débridement or repair, predicted 35% of postoperative MHHS [20], and generalized severe cartilage lesions intraoperatively led to high rates of arthroplasty within 3 years of arthroscopy [12].…”
Section: Discussionmentioning
confidence: 99%
“…The eight questions measure domains of pain, gait function, and functional activities. The scale has high construct validity [21,24]. Scores range from 0 …”
Section: Methodsmentioning
confidence: 99%
“…Two-tailed, independent t-tests were used to assess differences in age and body mass index (BMI) between sexes, and Fisher exact tests were used to determine if the sexes differed by preoperative diagnosis or prevalence of Dorr type A, B and C femurs. In addition, modified Harris Hip Scores [9] were recorded for each patient preoperatively, as well as six weeks and one year after surgery, and were compared using Mann-Whitney tests. SPSS version 15.0 (SPSS Inc., Chicago, IL, USA) was used to perform all analyses, and p≤0.05 was considered significant.…”
Section: Methodsmentioning
confidence: 99%
“…Hip arthroscopy has emerged as a minimally invasive approach to correct these bony abnormalities as well as their sequelae that may be precursors to OA. Specific techniques reported in the literature include femoral osteoplasty for cam-type FAI [3,7,18,25], acetabular rim-trimming for pincer-type FAI [26,40], labral débridement [8,22,29,30,33] and repair [24,28], and osteochondral defect débridement and microfracture [18,27,36].…”
Section: Introductionmentioning
confidence: 99%